DEVELOPMENT OF PAMUSI ONLINE GAME MEDIA OF GREATEST COMMON DIVISOR AND LEAST COMMON MULTIPLE IN ELEMENTARY SCHOOL - Quriana, Intan Maulida; Murti, Rahayu Condro; Bayan, Umar (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
The research started from the problem of online learning which requires learning media to motivate students to increase their interest in learning. Researchers developed mathematics learning media based on the online game PAMUSI on the material Lowest Common Multiple (LCM) and Greatest Common Factor (GCF). This research aims to find out the influence and feasibility of the PAMUSI online game media on GCF and LCM material in class IV at Tegalpanggung Elementary School. The research method uses Research and Development (RnD) with the ADDIE development model. The stages in this research include analysis, design, development, implementation and evaluation. The subjects of this research were fourth grade students at Tegalpanggung Elementary School. Data collection techniques use interviews, observation, and literature study. The analysis used is qualitative descriptive analysis. The results of the validator research showed that the PAMUSI online game learning media was suitable for use to increase interest in learning. The results of material validation obtained an average score of 4.3 in the "very good" category and media validation obtained an average score of 4.95 in the "very good" category. Limited field trials obtained an average score of 2.86 from student responses using the reference scale of three N-Gain formulas in the "high" category and an average score of 3.98 from teacher responses using four scale conversions in the "very" category. good category". This learning media motivates students to learn mathematics independently, especially HCF and LCM material because students are more challenged by playing PAMUSI online game-based learning media.Penelitian berawal dari permasalahan pembelajaran daring yang memerlukan media pembelajaran untuk memotivasi siswa dalam meningkatkan minat belajar. Peneliti mengembangkan media pembelajaran matematika berbasis game online PAMUSI pada materi Kelipatan Persekutuan Terendah (KPK) dan Faktor Persekutuan Tertinggi (FPB). Penelitian ini bertujuan untuk untuk mengetahui bagaimana pengaruh dan kelayakan media game online PAMUSI pada materi FPB dan KPK di kelas IV SD Tegalpanggung. Metode penelitian menggunakan Research and Development (RnD) dengan model pengembangan ADDIE. Tahapan dalam penelitian ini meliputi analisis, desain, pengembangan, implementasi, dan evaluasi. Subyek penelitian ini adalah siswa kelas IV SD Tegalpanggung. Teknik pengumpulan data menggunakan wawancara, observasi, dan studi literatur. Analisis yang digunakan adalah analisis deskriptif kualitatif. Hasil penelitian validator diperoleh hasil bahwa media pembelajaran game online PAMUSI layak digunakan ntuk meningkatkan minat belajar. Hasil validasi materi memperoleh skor rata-rata 4,3 dengan kategori “sangat baik” dan validasi media memperoleh skor rata-rata 4,95 dengan kategori “sangat baik”. Uji coba lapangan terbatas memperoleh skor rata-rata sebesar 2,86 dari respon siswa dengan menggunakan skala acuan tiga rumus N-Gain pada kategori “tinggi” dan skor rata-rata sebesar 3,98 dari respon guru dengan konversi empat skala pada kategori “sangat kategori baik". Media pembelajaran ini memotivasi siswa untuk belajar matematika secara mandiri khususnya materi FPB dan KPK dikarenakan siswa lebih tertantang memainkan media pembelajaran berbasis game online PAMUSI.